Analisis Pengaruh Biaya Preliminaries Terhadap Produktivitas Karyawan pada Proyek-Proyek PT. X - Clara Devina; Eddy Herjanto (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
PT.X is a contractor that has productivity problem that is affected by the cost of preliminaries cost. Preliminaries cost for PT. X is divided into 5 parts consisting of employee costs, general costs, financial costs, preparation costs and equipment costs. Employee costs have the largest portion of the cost of other preliminaries. In this study, the authors intend to review the effect of cost preliminaries on productivity in PT. X. The results of the research show that employee costs are 43% of the total cost of preliminaries and 5% of the VOW value. Further research shows that the building type of the project, the number of employees, and employee salaries have a positive effect on the productivity value of a project. The strategy that companies can implement to increase productivity is to set project productivity targets of 480 million / person / month and 45 rp / rp.